2019
DOI: 10.3310/hsdr07210
|View full text |Cite
|
Sign up to set email alerts
|

Care bundles to reduce re-admissions for patients with chronic obstructive pulmonary disease: a mixed-methods study

Abstract: Background Chronic obstructive pulmonary disease (COPD) is the commonest respiratory disease in the UK, accounting for 10% of emergency hospital admissions annually. Nearly one-third of patients are re-admitted within 28 days of discharge. Objectives The study aimed to evaluate the effectiveness of introducing standardised packages of care (i.e. care bundles) as a means of improving hospital care and reducing re-admissions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…We therefore estimated the cost effectiveness of both admission and discharge care bundles using observational patient-level data from 14 hospital sites located in England and Wales. This cost-effectiveness study was part of a wider project evaluating the effectiveness of care bundles for acute exacerbations of COPD [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore estimated the cost effectiveness of both admission and discharge care bundles using observational patient-level data from 14 hospital sites located in England and Wales. This cost-effectiveness study was part of a wider project evaluating the effectiveness of care bundles for acute exacerbations of COPD [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…We undertook a multi-method evaluation to address this knowledge gap 10–12. Our quantitative findings indicated that admission and discharge bundles for COPD had little impact on patient outcomes, including readmissions and mortality or healthcare costs, although bundles did appear to be associated with a reduced number of subsequent attendances at the emergency department.…”
Section: Introductionmentioning
confidence: 99%
“…Our quantitative findings indicated that admission and discharge bundles for COPD had little impact on patient outcomes, including readmissions and mortality or healthcare costs, although bundles did appear to be associated with a reduced number of subsequent attendances at the emergency department. Variability in bundle structure and implementation create challenges in ascertaining the impact of COPD care bundles on patient outcomes 11 12. Within the evaluation, we conducted a qualitative study which examined how bundles were delivered and how staff perceived bundles to impact the process of patient care 10 12.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations